2008
DOI: 10.1111/j.1524-4725.2008.34318.x
|View full text |Cite
|
Sign up to set email alerts
|

“Reading Man Flap” Design for Reconstruction of Circular Infraorbital and Malar Skin Defects

Abstract: The reading man flap can be used to reconstruct malar and infraorbital circular defects with good cosmetic results and without creating any tractional forces to the eyelids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 28 publications
(42 reference statements)
0
17
0
Order By: Relevance
“…In comparison with the Limberg flap in the RMF, the scar length and the total scar area were more pronounced, but no additional healthy skin had to be discharged, furthermore it created smaller traction forces. The bilobed flap had the longest scar length, the highest total scar area, and most healthy skin removed in comparison with the other two flaps . However, as described by the authors, the classical RMF is limited to circular skin defects…”
Section: Introductionmentioning
confidence: 78%
“…In comparison with the Limberg flap in the RMF, the scar length and the total scar area were more pronounced, but no additional healthy skin had to be discharged, furthermore it created smaller traction forces. The bilobed flap had the longest scar length, the highest total scar area, and most healthy skin removed in comparison with the other two flaps . However, as described by the authors, the classical RMF is limited to circular skin defects…”
Section: Introductionmentioning
confidence: 78%
“…5 They have postulated that the reading man flap is the most suitable among these techniques in terms of total scar area and length and suggested that this new flap design can be used to reconstruct malar and infraorbital circular defects with good cosmetic results without creating any traction forces on the eyelids. Seyhan and Caglar compared this flap to the Limberg and bilobed flaps.…”
Section: Discussionmentioning
confidence: 99%
“…A circular type of defect, which is usually encountered after the surgery, should be converted to either elliptical or rhomboid type for reconstruction. However, to change the shape of the defect, excision of healthy tissues around the defect is inevitable, not to mention the risk of long scar, dog‐ear formation or trapdoor deformity 5 …”
Section: Discussionmentioning
confidence: 99%